An Archaeological Analysis of Ruined Rural Settlements around a village near Ardabil City (Case Study: Viyand Settlement, Guran Site and Yel Suyi Site) - Habib Shahbazi Shiran (Anastasis: Research in Medieval Culture and Art)
Ardabil province, with its North-South expansion in North- Western Iran and the Eastern part of the Azerbaijani plateau, includes intermountain plains and high mountains. Due to its diverse ecosystem and various latitudes, this province has been a suitable platform for human settlement in different periods of human life. According to archeological evidence, the region of Ardabil has been inhabited since the 1st millennium BC. The whole area is covered with ancient hills, or in other words, settlement areas, which were once fortresses or towns or villages. According to the existing ancient monuments, this region was one of the leaders of this civilization in the early days and the beginning of the formation of human civilizations, especially in the field of prehistorical civilizations, and this situation has continued during historical periods. As information and historical documents show, this region has played an effective and important role in attracting civilizations and transferring it to the other side, as well as spreading its civilization to the adjacent areas, as this has been one of the most important centers of civilization during the Sassanid era. In the Islamic era, it had a special position. In any case, although the evidence from this area is very rare, there is no doubt that today, a wide variety of ancient monuments from each of the past civilizations cover the entire plain. Considering the above points, it seems that the Ardabil region is a hidden and covered page of the history of Iran and will be the solution to deciphering ambiguous events,being seen as a possible means of communication among known events. The purpose of this paper is to show the physical and archeological nature and the dark and hidden corners of rural and urban settlements such as Viyand, Guran and Yel Suyi (which unfortunately have only a few traces left today). This research is a descriptive-analytical study based on library, documentary, and field studies.